Ekstrak Daun Sambiloto (Andrographis Paniculata) Dalam Mengendalikan Pertumbuhan Bakteri Aeromonas hydrophila, Edwardsiella tarda dan Jamur Saprolegnia sp. Secara In Vitro - Lihardo Sinaga; Dwi Suryanto; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
This study was aimed to know antimicrobial potential of extract of sambiloto’s Leaf (Andrographis paniculata) to bacteria Aeromonas hydrophila, Edwardsiella tarda and Saprolegnia sp. and to know the extract toxicity to brine shrimp (Artemia salina). Sambiloto’s leaf was extracted using methanol, ethyl acetate and n-Hexane. Antimicrobial activity test was done using diffusion discs method. To know the compunds contained in the extract phytochemical test was conducted. The chemical compound test showed that extract of sambiloto’s leaf contained terpenoid/steroid and saponin. The extracts inhibit the growth of Aeromonas hydrophila and Edwardsiella tarda but Saprolegnia sp. Ethyl acetate extract showed to have maximum inhibition to Aeromonas hydrophila of 9,11 – 10,78 mm and Edwardsiella tarda of 6,10 – 9,50 mm respectivity. All extract showed to have LC50<1000 μg/ml. Toxicity of n-hexane extract was highest to Artemia salina with LC50 of 118,6 ppm.Keywords : Antimicrobial activity, Aeromonas hydrophila, Edwardsiella tarda Andrographis paniculata, Saprolegnia sp.